Randomized, Placebo-Controlled Phase 2b Study to Evaluate the Safety and Efficacy of Recombinant Human Lecithin Cholesterol Acyltransferase in Acute ST-Segment–Elevation Myocardial Infarction: Results of REAL-TIMI 63B. Issue 12 (30th August 2022) - Bonaca, Marc P.; Morrow, David A.; Bergmark, Brian A.; Berg, David D.; Lima, Joao A.C.; Hoffmann, Udo; Kato, Yoko; Lu, Michael T.; Kuder, Julia; Murphy, Sabina A.; Spinar, Jindrich; Oude Ophuis, Ton; et al.
Abstract : Background: High-density lipoprotein plays a key role in reverse cholesterol transport. In addition, high-density lipoprotein particles may be cardioprotective and reduce infarct size in the setting of myocardial injury. Lecithin-cholesterol acyltransferase is a rate-limiting enzyme in reverse cholesterol transport. MEDI6012 is a recombinant human lecithin-cholesterol acyltransferase that increases high-density lipoprotein cholesterol. Administration of lecithin-cholesterol acyltransferase has the potential to reduce infarct size and regress coronary plaque in acute ST-segment–elevation myocardial infarction. Methods: REAL-TIMI 63B (A Randomized, Placebo‑controlled Phase 2b Study to Evaluate the Safety and Efficacy of MEDI6012 in Acute ST Elevation Myocardial Infarction) was a phase 2B multinational, placebo-controlled, randomized trial. Patients with ST-segment–elevation myocardial infarction within 6 hours of symptom onset and planned for percutaneous intervention were randomly assigned 2:1 to MEDI6012 (2- or 6-dose regimen) or placebo and followed for 12 weeks. The primary outcome was infarct size as a percentage of left ventricular mass by cardiac MRI at 10 to 12 weeks, with the primary analysis in patients with TIMI Flow Grade 0 to 1 before percutaneous intervention who received at least 2 doses of MEDI6012. The secondary outcome was change in noncalcified plaque volume on coronary computed tomographic angiography from baseline to 10 to 12 weeks with the primary analysis in patients who received all 6 doses of MEDI6012. Results: A total of 593 patients were randomly assigned. Patients were a median of 62 years old, 77.9% male, and 95.8% statin naive. Median time from symptom onset to randomization was 146 (interquartile range [IQR], 103–221) minutes and from hospitalization to randomization was 12.7 (IQR, 6.6–24.0) minutes, and the first dose of drug was administered a median of 8 (IQR, 3–13) minutes before percutaneous intervention. The index myocardial infarction was anterior in 69.6% and TIMI Flow Grade 0 to 1 in 65.1% of patients. At 12 weeks, infarct size did not differ between treatment groups (MEDI6012: 9.71%, IQR 4.79–16.38; placebo: 10.48%, [IQR, 4.92–16.61], 1-sided P =0.79. There was also no difference in noncalcified plaque volume (geometric mean ratio, 0.96 [95% CI, NA–1.10], 1-sided P =0.30). There was no significant difference in treatment emergent serious adverse events. Conclusions: Administration of MEDI6012 in patients with acute ST-segment–elevation myocardial infarction did not result in a significant reduction in infarct size or noncalcified plaque volume at 12 weeks. MEDI6012 was well tolerated with no excess in overall serious adverse events. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03578809.